Advancements in Accident Tolerance Fuel: A New Horizon in Nuclear Safety - Ngarayana, I Wayan; Kurniawan, Rusbani; Rachman, Agus Nur; Nugraha, Eka Djatnika; Ekaranti, Egnes; Andani, Ika Wahyu (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
Accident Tolerant Fuels (ATFs) represent a significant advancement in nuclear safety, offering the potential to mitigate the risks associated with nuclear reactor accidents. This paper provides a comprehensive overview of the development and current state of ATF technology, tracing its evolution and highlighting key technological milestones. Through an analysis of various case studies, we examine the practical application and performance of ATFs in real-world scenarios. Despite the promising capabilities of ATFs, their development and deployment are not without challenges. We delve into the technical, regulatory, and economic hurdles that must be overcome to realize the full potential of ATFs. Looking ahead, we explore the prospects of ATFs, discussing potential advancements and their implications for the nuclear industry. The findings of this paper underscore the transformative role of ATFs in enhancing nuclear reactor safety and charting a new horizon in nuclear technology.